Patient with Carcinoid Syndrome and Severe Cardiac Disease with Both Tricuspid an Pulmonary Lesions - Nitu, Ileana; Burcea, Iulia Florentina; Greere, Daniela; Croitoru, Adina; Poiana, Catalina (Archives of Clinical and Medical Case Reports, 2022)
Introduction: Carcinoid Heart Disease (CHD) is a rare cardiac manifestation occurring in patients with advanced Neuroendocrine Tumours (NET) and the carcinoid syndrome, usually involving the right-sided heart valves and eventually leading to right heart failure. The additional burden of cardiac dysfunction heralds a steep decline in quality of life and survival, the prompt recognition of this disease being therefore of the utmost importance. Case summary: We present the case of a 57 year old female patient diagnosed in 2016 with carcinoid tumor of the proxymal ileum (Grade 2 NET ki 67 8%) and liver metastasis. She underwent surgery with both tumor and secondary determinations resection, followed by chemotherapy in the same year. The patient comes to our clinic in February 2019, complaining in the last 5 months of abdominal pain associated with flushing of the face, simetric peripheral edema, progressive limitation in effort, appearance of dyspnea on moderate exertion and dry caugh. The transthoracic echocardiography detected severe dilation of the right chambers, systolic dysfunction of the right ventricle, tricuspid disease with severe regurgitation and mild stenosis. The echocardiography also revealed double pulmonary lesion with moderate regurgitation and mild stenosis. Endocrine evaluation revealed high levels of serum markers for Neuroendocrine Tumor (NET): serotonin (1543 ng/ml), cromogranin A (291 ng/ml), urinary level of 5-hydroxyindolacetic acid (84 mg/24 h). Discussion: The carcinoid syndrome was considered to be the cause of the right-heart disease, regarding the fact that echocardiographic features suggested primary valvular lesions. Somatostatin analogue treatment was started with significant improvement in symptoms and NET markers, thus allowing cardiac surgery a month later with remission of symptom